Understanding the humanitarian world - Maxwell, Daniel G.; Gelsdorf, Kirsten Heidi (Routledge global institutions series, 2019)
Conflict and disaster have been part of human history for as long as it has been recorded. Over time, more mechanisms for responding to crises have developed and become more systematized. Today a large and complex 'global humanitarian response system' made up of a multitude of local, national and international actors carries out a wide variety of responses. Understanding this intricate system, and the forces that shape it, are the core focus of this book. Daniel G Maxwell and Kirsten Gelsdorf highlight the origins, growth, and specific challenges to, humanitarian action and examine why the contemporary system functions as it does. They outline the main actors, explore how they are organised and look at the ways they plan and carry out their operations. Interrogating major contemporary debates and controversies in the humanitarian system, and the reasons why actions undertaken in its name remain the subject of so much controversy, they provide an important overview of the contemporary humanitarian system and the ways it may develop in the future. This book offers a nuanced understanding of the way humanitarian action operates in the 21st century. It will be essential reading for anyone with an interest in international human rights law, disaster management and international relations